Struktur Kepemilikan dan Kebijakan Dividen pada Perusahaan LQ45 di Bursa Efek Indonesia (BEI) - Hasnawati, Sri; Dalimunthe, Nindytia Puspitasari; Faisol, Ahmad (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
This study examines the relationship between ownership structure and dividend policy within the context of the LQ45 Index for the year 2021. Focusing on 33 constituent firms, the research analyzes the effects of public, institutional, and managerial ownership on corporate dividend decisions. Employing an Ordinary Least Squares (OLS) regression model, the analysis demonstrates a positive correlation between public ownership and dividend payouts, while revealing a negative association between institutional ownership and dividend policy. Conversely, the study finds no statistically significant impact of managerial ownership on dividend policy. This non-significance is potentially explained by the comparatively low average level of managerial ownership and a focus on reinvesting free cash flow. Additionally, the findings suggest a potential alignment between institutional and managerial ownership in favoring lower dividend distributions.